PENGARUH PANDEMI COVID-19 TERHADAP PENGEMBANGAN ANAK DI SEKOLAH - Pipit Irawati (Pusat Riset dan Inovasi Nasional, 2023)
The most noticeable impacts of the Covid-19 pandemic are school closures and online distance learning (PJJ). Online learning uses the Internet to provide teaching materials to students. Barriers to online learning are felt by both teachers and students, with streaming learning via Zoom sometimes having unstable internet connections. Another obstacle to online learning between teachers and students is the teacher-student relationship. You look nervous because you get stuck in the Zoom application. A barrier to online learning between students and parents is that it is difficult for working parents to tutor their children because they are working. The impact of online learning itself takes the form of reduced learning ability and changes in student behavior. The purpose of this non-research journal is that schools need new strategies to meet their post-pandemic educational goals. In order to overcome this, it is necessary to develop human resources by implementing education that reflects the cultural characteristics of the country. Education must respond not only to global requirements, but also to developments in digital technology.